Upaya Peningkatan Kemampuan Berbahasa Anak melalui Kegiatan Bercerita Pengalaman Sendiri di TK Pertiwi II Cemeng - Sulasih, Sulasih (Universitas Pendidikan Indonesia Kampus Serang, 2022)
The aims of this study were: (1) to describe the steps of the learning process that occurs when using storytelling activities, (2) to describe the steps of storytelling techniques that can be used in learning activities, (3) to find out the situation after participating in storytelling activities from one's own experience. This research is classroom action research that wants to reveal the increase in children's language skills through story telling activities using two cycles. This research started from January to June 2020. The research location was in Pertiwi II Cemeng Kindergarten, Sambungmacan District, Sragen Regency with 20 research subjects. Based on data from the results of children's language skills before being given action by using storytelling activities, it shows that in storytelling activities 15% of children are able to memorize stories, 25% of children are able to understand story content, and 30% of children appear language skills in pre-cycle conditions. Based on data in cycle I, 30% of children showed the ability to memorize stories, 40% of children were able to understand story content, and language skills in storytelling activities increased to 45% of children. The results of children's language skills in cycle II observed that 60% of children could memorize stories, 75% of children were able to understand the contents of the story, and 85% of children showed language skills in storytelling activities. This shows the effectiveness of this storytelling activity in improving children's language skills. This activity can be an alternative solution for teachers who experience the same problem